Putting Literacy Centers to Work: A Novice Teacher Utilizes Literacy Centers to Improve Literacy Instruction - Rebecca Stout (Networks: An Online Journal for Teacher Research, 2009)
“Girl, you have got to do something about that reading lesson!” After observing a reading lesson, my mentor shared how most of my students were off-task. She pointed out how some students were playing with the supplies on their tables and some were playing with supplies under the table. She suggested that I make the lesson more hands-on and interactive, possibly utilizing manipulatives, to keep the students engaged. My frustration mounted as I listened to these words of advice from my mentor because the lesson that I was giving was a scripted Reading First lesson. Reading First is a grant from the federal government that provides funding for both instructional and assessment materials as well as professional development for teachers. My quandary led me to compare my school’s Reading First Program with my prior teaching experiences.